Determinants of Accounting Practice in Micro and Small Enterprises: Evidence from Ethiopia - Enyew Mulu Zelie; Tamiru Aniley Alebachew; Kenubish Asrat Alem (Universitas Hayam Wuruk Perbanas, 2020)
This study assesses the factors determining accounting recordkeeping practices among micro and small enterprises in Ethiopia's South Western Wollo region. It has been noted that, despite the enormous importance of accounting recordkeeping, the practice is still inadequate in micro and small businesses. This study used cross-sectional primary data collected from 343 micro and small enterprises. An ordered logistic regression analysis method was employed to analyze the explanatory variable's effect (education level, number of employees, frequency of transactions, size of the firm, and age of the firm) on micro and small enterprises' accounting practice. The study results show that the education level, the number of employees, the frequency of transactions, and the firm's size have a statistically significant and positive effect on the accounting practice of micro and small enterprises. On the other hand, the firm's age is found to have no statistically significant effect on micro and small enterprises' accounting practice. This study helps micro and small enterprises by showing the significant factors that affect their accounting practice and working towards better reporting and decision-making habits.